Self-determined motivation and subjective well- being of adapted sport athletes members of Special Olympics - Batista, Marco (2019)
Adapted sport is an organized participation whose objective is to obtain improvement in physical and psychic conditions, that is, it represents one of the most important factors promoting educational success, inclusion and psychosocial development. The objective of this study was to evaluate the self-determined competences for the practice of sport and the levels of well-being, in athletes with Intellectual and Developmental Difficulties (DID) participating in the Special Olympics in Portugal, to be correlated as variables in study and which variables of self-determination are predictors of subjective well-being in this collective. Participated 54 Adapted Sport athletes, with DID, belonging to Portuguese Private Social Solidarity Institutions, participating in the Special Olympics competitive regime. Of the 54 athletes, 12 are female (22.22%) and 42 males (77.78%), aged between 11 and 53 years old (ẋ = 29.57 and SD = 10.59). For the data collection, the following validated scales were applied for the Portuguese population, The Basis Psychological Needs in Exercise Scale, The Behavioural Regulation in Sport Questionnaire, The Satisfaction with Life Scale, and The Positive and Negative Affect Scale. The athletes with intellectual and developmental difficulties (DID) participating in the Special Olympics revealed a high self-determined motivation for sports practice, and their subjective well- being was high enough and dependent on their levels of autonomous motivation. The regression models revealed that the best predictor of subjective well-being in this group was the autonomous motivation.